Integrating improved goat breeds with new varieties of sweet potatoes and cassava in the agro-pastoral systems of Tanzania: A gendered analysis - Saghir, P.; Njuki, Jemimah; Waithanji, Elizabeth M.; Kariuki, Juliet B.; Sikira, A. (International Livestock Research Institute, 2012)
This paper focuses on analysing gender issues in livestock and root crop production. Qualitative data for the study was collected through gender disaggregated group discussions (GDs) in two districts, Mvomero and Kongwa in Tanzania. Data were collected from 4 communities representing the four villages—Wami Luhindo and Kunke in Mvomero, and Masinyeti and Ihanda in Kongwa respectively. A total of 12 GDs were conducted involving 224 men and women who participated in the GDs. The qualitative data were analysed descriptively and by using measures such as percentages, tables, pie, bar charts and Venn diagrams. The study found that men owned all the goats and made all goat related decisions unilaterally. Women were by far less likely than men to own not only goats, but also livestock in general. On management of goats, an important set of differences in activities is associated with gender as well as with age. Changing livelihood opportunities such as rural–urban migration were identified as a factor that influenced gender and goat management and this increases workload for women. On decision-making over goats, women have limited control over decisions on sale and use of incomes generated from sale of goats. Ownership of crops between men and women is quite distinct, and depends on the market prices of crops and yield of the crop they grow for cash. Men own cash crops or crops for cash whereas women own subsistence or food crops for home consumption. Wealth status had a direct relation with individual decision-making on crops, rich men and women decided on what crops to cultivate, whereas non-rich farmers worked on wealthy farmers’ farms as casual labourers. Perceptions of women and men on the potential benefits of integrating root crops and goat varied. Men perceived value addition resulting from owning dairy goats and the attendant increase in income for them whereas women perceived change in status quo and increase workload resulting from stall goat management activities. Some participants explained that the anticipated increase in men’s real income could come about either through men accessing women’s income, or more commonly, women using their earnings to substitute men’s expenditure on household needs and children’s education. The study concluded that there are gender differences on perceived potential of integrating root crops and dairy goat production, as prevailing tradition may limit women’s participation. The beneficiaries expressed the timeliness of CGP project and exhibited willingness to partake in the project and ensure equitable benefits for participants if participatory gender training and awareness is ensured at both the household and community level. The study recommended that investing in rigorous gender trainings for both women and men, to initially sensitize them on the importance of including both women and men in development projects and sustain their continued understanding of the importance of gender inclusive activities.